Epidemiology and genetic characterization of Alternaria alternata causing leaf spot in Fragaria × ananassa - Nasir Mehmood; Abid Riaz; Salman Ghuffar; Sadaf Anwaar; Nyla Jabeen; Isha Shaheen; Muhammad Qasim; Salma Saeed Khan; Muhammad Rauf; Tauseef Anwar; Huma Qureshi; Ghadah Salim Abusalim; et al. (Fungal Biology, 2025)

An updated landscape on nanopharmaceutical delivery for mitigation of colon cancer - Maria Shahzad; Huma Hameed; Ayesha Amjad; Mahtab Ahmad Khan; Inaba Shujaat Qureshi; Anam Hameed; Asad Saeed; Rabia Munir (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Mines to moana: Hydrochemical legacies in a historically mined watershed - Adam Hartland; Madison Farrant; Sebastian N. Höpker; Dorisel Torres Rojas; Huma Saeed; Aldrin Rivas; Andrew La Croix; Megan Grainger; Tanya O'Neill (Applied Geochemistry, 2024)

Comprehensive chemical profiling with UHPLC-MS, in-vitro, in-silico, and in-vivo antidiabetic potential of Typha domingensis Pers; A novel source of bioactive compounds - Rizwana Dilshad; Kashif-ur-Rehman Khan; Rihana Dilshad; Saeed Ahmad; Huma Rao; Umair Khurshid; Sultan Ahmad; Maqsood Ahmad; Hafiz Muhammad Usman Abid; Muhammad Kashif Zaman; Rabia Nisar; Saharish Khaliq; et al. (South African Journal of Botany, 2024)

Protective effect of chemically characterized extract of Viola stocksii Boiss. against breast cancer and vincristine induced neuropathic pain by alleviation of oxidative stress and inflammatory markers - Abdul Basit; Chitchamai Ovatlarnporn; Huma Rao; Saeed Ahmad; Warayuth Sajomsang; Jirada Singkhonrat; Safiullah Khan; Kifayat Ullah Khan; Hassan Shah; Kashif ur Rehman Khan (Food Bioscience, 2023)

Unraveling the effects of zinc sulfate nanoparticles and potassium fertilizers on quality of maize and associated health risks in Cd contaminated soils under different moisture regimes - Muhammad Umair; Sehrish Huma Zafar; Mumtaz Cheema; Rashid Minhas; Abdul Manan Saeed; Muhammad Saqib; Muhammad Aslam (Science of The Total Environment, 2023)

Immunoreactivity of Brugia malayi Calreticulin and Its Domains with Sera of Different Categories of Bancroftian Filarial Patients - Sunita Yadav; Smita Gupta; Mohd Saeed; Huma Mustafa; Jitendra Kumar Saxena; Puvvada Kalpana Murthy (Acta Parasitologica, 2022)

Isolation of tyrosine derived phenolics and their possible beneficial role in anti-inflammatory and antioxidant potential of Tithonia tubaeformis - Noor Ul Ain Nawaz; Muhammad Saeed; Khalid Mohammed Khan; Irfan Ali; Huma Aslam Bhatti; Sabi-Ur-Rehman; Muhammad Shahid; Shaheen Faizi (Natural Product Research, 2021)

Impacts of methyl jasmonate and phenyl acetic acid on biomass accumulation and antioxidant potential in adventitious roots of Ajuga bracteosa Wall ex Benth., a high valued endangered medicinal plant - Sabahat Saeed; Huma Ali; Tariq Khan; Waqas Kayani; Mubarak Ali Khan (Physiology and Molecular Biology of Plants, 2017)

In search of a potential diagnostic tool for molecular characterization of lymphatic filariasis - Mohd Saeed; Mohd Adnan; Saif Khan; Eyad Al-Shammari; Huma Mustafa (Acta Parasitologica, 2016)
Lymphatic filariasis (LF) is a chronic disease and is caused by the parasites Wuchereria bancrofti (W. bancrofti), Brugia malayi (B. malayi) and Brugia timori (B. timori). In the present study, Setaria cervi (S. cervi), a bovine filarial parasite has been used. Previously, it has been reported that the S. cervi shares some common proteins and antigenic determinants with that of human filarial parasite. The larval stages of filarial species usually cannot be identified by classical morphology. Hence, molecular characterization allows the identification of the parasites throughout all their developmental stages. The genomic DNA of S. cervi adult were isolated and estimated spectrophotometrically for the quantitative presence of DNA content. Screening of DNA sequences from filarial DNA GenBank and Expressed Sequence Tags (EST’s) were performed for homologous sequences and then multiple sequence alignment was executed. The conserved sequences from multiple sequence alignment were used for In Silico primer designing. The successfully designed primers were used further in PCR amplifications. Therefore, in search of a promising diagnostic tool few genes were identified to be conserved in the human and bovine filariasis and these novel primers deigned may help to develop a promising diagnostic tool for identification of lymphatic filariasis.

Involvement of cyclooxygenase, phospholipase C and MAP kinase pathways in human platelet aggregation mediated by the synergistic interaction of adrenaline and PAF - Sheikh A. Saeed; Huma Rasheed; Zahra A. Hoodbhoy; Simeen R. Pasha; Zohair Mapara; Haresh Kumar; Bukhtiar H. Shah (Inflammopharmacology, 2001)